Islamic Education Approach: Fethullah Gulen's Perspective - Ahmad Maruf; Sumantri, Dwipa (Linguanusa : Social Humanities, Education and Linguistic, 2023)
Introduction to The Problem : Ideal education is viewed as a comprehensive process that fosters the full development of human potential, particularly intellectual growth, within educational institutions like schools. It emphasises the transmission of knowledge, traits, and abilities from one generation to the next. Nevertheless, contemporary education is frequently regarded as being surpassed, tending towards dehumanisation, and being accessible solely to the majority. Contemporary school education sometimes fails to ensure equitable chances for all pupils, particularly those who do not fall under the classification of "gifted children" (Suryadi, 2018). According to the perspective of critical education, it is advocated that education should adopt a more humanistic approach, emphasising on learning that promotes critical consciousness and social equity (Nuryatno, 2011). Purpose : The objective of education should transcend limitations and actively contribute to the betterment of society. Furthermore, the concepts put out by influential individuals like Gulen hold great significance and can serve as a foundation for rectifying shortcomings in education. Design/methods/approach: This study employed a qualitative methodology, involving the collection of descriptive data through written or spoken words from individuals or through the observation of their behaviour. This study also references the perspectives of Bodgan and Taylor regarding research methodologies that provide descriptive data, as well as Sugiyono's explanation that qualitative knowledge can be conveyed through many mediums such as images, sentences, and words (Pratiwi, 2017). In order to obtain research sources, researchers seek references from diverse publications with comparable titles, obviating the necessity of conducting field research. Findings : This study will analyse the viewpoints of these individuals under the topic of Islamic Education Approach: Fethullah Gulen's Perspective. Gülen viewed education as a transformative journey that guides individuals towards the attainment of human excellence, encompassing both intellectual and spiritual dimensions. Hence, the principles of Islam should be employed as a crucial framework to prevent errors in life. Education, in this context, is regarded as a significant obligation to assist others with the principles of empathy and benevolence (Sulaiman, 2016). Gülen characterised education as a system that equips individuals with the necessary skills and knowledge to adapt to the evolving world, while upholding Islamic beliefs. Research implications/limitations: Education should be grounded in the ideas of both science and religion, with a strong emphasis on the significance of love, tolerance, and discourse. Nevertheless, Gulen imposed restrictions on educational freedom grounded in religious tenets. Gulen has spearheaded efforts in educational development institutions, such as schools, to enhance the cohesion and resilience of communities. Originality/value : This study gives novel perspectives on Islamic teaching methodologies from the viewpoint of Fethullah Gulen, providing potential remedies for existing educational difficulties. This research proposes an educational framework that is inclusive, humanist, and relevant to current requirements. It takes into consideration the principles of science and religion, while emphasising the significance of love, tolerance, and conversation.